I Intensifikasi Tanaman Berkhasiat Obat Keluarga pada Masyarakat di Desa Kiram : Intensification Of Family Medicinal Plants In The Community In Kiram Village - Radam, Rosidah; Suyanto, Suyanto; Susilawati, Susilawati; Nugroho, Yusanto; Pujawati, Eny Dwi; Rachmawati, Normela; Payung, Damaris; Mufidah, Mufidah (Kayuh Baimbai: Jurnal Pengabdian Masyarakat, 2024)
TOGA or family medicinal plants are plants with medicinal properties that are planted in home gardens. TOGA can provide health and economic benefits for residents. Based on observations in Kiram Village, so far the people of Kiram Village, especially the people of RT 01, have not used their yard land optimally. Only some village residents use their yard for planting TOGA and it is not optimal. Therefore, it is necessary to provide outreach, training and assistance for TOGA intensification to the Kiram Village community. The aim of this outreach and assistance activity is to improve the function of home gardens through the application of TOGA, empower the community with new knowledge and skills in TOGA cultivation and increase community knowledge of the benefits of TOGA for health. Methods: Activities carried out include outreach and counseling, training and mentoring, as well as monitoring and evaluation. After the counseling and mentoring activities, there was an increase in public knowledge regarding various types of TOGA, the use of TOGA and how to cultivate TOGA. The public also understands more about the benefits of TOGA for health. Before the community service activity was carried out, only three houses had their yards planted with TOGA, whereas after the activity there were 15 houses whose yards had been used by the community to plant TOGA.